Фінансово-правові засади формування спроможних бюджетів територіальних громад - Коробцова, Д. В.; Korobtsova, D. V.; ORCID: http://orcid.org/0000-0002-4753-7433; Міщенко, Л. В.; Mishchenko, L. V.; ORCID: http://orcid.org/0000-0003-4906-8287 (Право і безпека. - 2021. - № 3 (82). - С. 159-165, 2021)
Досліджено бюджетно-правові відносини, які складаються на рівні формування бюджетів об’єднаних територіальних громад, і визначено фінансово-правові підстави формування спроможних бюджетів. Уточнено поняття «бюджет ОТГ» і сутність поняття «спроможний бюджет». Спираючись на історичний досвід розвитку бюджетних відносин в Україні та зарубіжний досвід, доведено необхідність формування спроможних бюджетів за рахунок альтернативних надходжень, а саме шляхом надання ОТГ прав щодо встановлення непрямих податків, регулювання пільг і податкових ставок, отримання доходів від господарської діяльності, а також від використання міжбюджетних трансфертів у потрібних обсягах та на визначені цілі. Обґрунтовано пропозиції щодо вдосконалення фінансового законодавства стосовно термінології та сутності бюджетної діяльності.

The formation of UTC budgets requires not only the improvement of the structure of tax revenues, as well as the analysis of revenues, but currently the use of intergovernmental transfers as important additional revenues of UTC budgets in modern research is the subject of discussion. The budgetary and legal relations which are formed at the level of formation of budgets of the united territorial communities are investigated, and the financial and legal bases of formation of capable budgets are defined. Examples of scientific research on various aspects of local finance as factors influencing the formation, distribution and use of national budget funds, as a legal institution and as a basis for comparative characteristics of domestic and foreign practice of local budgeting, etc. are considered. The main problems that arise in the way of optimizing the revenue policy of local budgets of the united territorial communities in the conditions of financial decentralization are described. The set of tasks on which the provision of financial capacity of the territorial community depends is analyzed. The main steps that the state must take to implement the budget decentralization reform effectively are identified. It is stated that during the formation of a promising united territorial community it is important to calculate its financial capacity in advance, which will allow to assess the benefits and risks of such association, determine the need for additional funds and streamlining expenditures, and to envisage its further functioning for the purpose of its socio-economic development. The concept of "UTC budget" and the essence of the concept of "capable budget" are specified. Based on the historical experience of budget relations in Ukraine and foreign experience, the need to form viable budgets at the expense of alternative revenues , namely by providing UTC rights to establish indirect taxes, regulate benefits and tax rates, income from business activities, and the use of intergovernmental transfers in the required amounts and for specific purposes is proved. Philosophical, general scientific and special methods of scientific cognition are used, and also formation of the balanced and substantiated income and expense parts of budgets in the volume sufficient for performance of the set tasks is found out. The legal bases for formation of the revenue part of the budget at the expense of both tax and non-tax revenues and financing of certain types of expenditures are analyzed. Proposals for improving the financial legislation regarding the terminology and essence of budget activities are substantiated.

Исследованны бюджетно-правовые отношения, которые складываются на уровне формирования бюджетов объединенных территориальных общин, и определены финансово-правовые основания формирования способных бюджетов. Уточнены понятие «бюджет ОТО» и сущность понятия «способный бюджет». Опираясь на исторический опыт развития бюджетных отношений в Украине и зарубежный опыт, доказана необходимость формирования способных бюджетов за счет альтернативных поступлений, а именно путем наделения ОТО правами по установлению косвенных налогов, регулированию льгот и налоговых ставок, получению доходов от хозяйственной деятельности, а также от использования межбюджетных трансфертов в нужных объемах и на определенные цели. Обоснованы предложения по совершенствованию финансового законодательства в отношении терминологии и сущности бюджетной деятельности.
Financial and legal bases for the formation of territorial communities capable budgets
Финансово-правовые основы формирования способных бюджетов территориальных общин
Коробцова, Д. В. Фінансово-правові засади формування спроможних бюджетів територіальних громад / Дар'я Вікторівна Коробцова, Ліна Володимирівна Міщенко // Право і безпека. - 2021. - № 3 (82). - С. 159-165. -DOI: https://doi.org/10.32631/pb.2021.3.18.
Коробцова Д. В., Міщенко Л. В. Фінансово-правові засади формування спроможних бюджетів територіальних громад. Право і безпека. 2021. № 3 (82). С. 159–165. DOI: https://doi.org/10.32631/pb.2021.3.18.
Korobtsova, D. V., & Mishchenko, L. V. (2021). Financial and Legal Bases for the Formation of Territorial Communities Capable Budgets. Law and Safety, 3(82), 159–165. https://doi.org/10.32631/pb.2021.3.18.
Keywords: Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; місцевий бюджет; местный бюджет; local budget; фінансова спроможність; финансовая состоятельность; financial capacity; доходи бюджетів; доходы бюджетов; budget revenues; бюджет об’єднаних територіальних громад; бюджет объединенных территориальных общин; budget of the united territorial communities; фінансово-правове регулювання; финансово-правовое регулирование; financial and legal regulation; спроможний бюджет; состоятельный бюджет; capable budget; податкові надходження; налоговые поступления; tax revenues; зарубіжний досвід; зарубежный опыт; foreign experience